Calculation of Android Based Eggtray Production Based Prices Using Moving Average Method (case Study of PT. Sinar Era Box Gresik) - Dani Marido; Rani Purbaningtyas; Mas Nurul Hamidah (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
The price of the staple production based on activities is how to determine a fee by way of tracing the activities of an organization the company in generating an item. This is intended so that the largest cost breakfast buffet in producing goods itself. In addition the existence of a desire of the company to produce goods and costs as effectively as possible. Tracking the cost of these activities through automatic menegement parties can manage cost effectiveness. To find out the price of a staple production of PT.Sinar Era Box Gresik, then on the basis of the research that's going on. Research carried out using moving average algorithm (moving average), while the data is the data that comes from the PT.Sinar Era Box Gresik. This research resulted in the value of the production cost of goods based on the average price moves in can be of any purchase of goods.